Haploidentical transplantation has a superior graft-versus-leukemia effect than HLA-matched sibling transplantation for Ph– high-risk B-cell acute lymphoblastic leukemia. Issue 8 (20th April 2022) - Fan, Menglin; Wang, Yu; Lin, Ren; Lin, Tong; Huang, Fen; Fan, Zhiping; Xu, Yajing; Yang, Ting; Xu, Na; Shi, Pengcheng; Nie, Danian; Lin, Dongjun; et al.
Abstract: Background: Compared with human leukocyte antigen (HLA)-matched sibling donor (MSD) transplantation, it remains unclear whether haploidentical donor (HID) transplantation has a superior graft-versus-leukemia (GVL) effect for Philadelphia-negative (Ph–) high-risk B-cell acute lymphoblastic leukemia (B-ALL). This study aimed to compare the GVL effect between HID and MSD transplantation for Ph– high-risk B-ALL. Methods: This study population came from two prospective multicenter trials (NCT01883180, NCT02673008). Immunosuppressant withdrawal and prophylactic or pre-emptive donor lymphocyte infusion (DLI) were administered in patients without active graft-versus-host disease (GVHD) to prevent relapse. All patients with measurable residual disease (MRD) positivity posttransplantation (post-MRD+) or non-remission (NR) pre-transplantation received prophylactic/pre-emptive interventions. The primary endpoint was the incidence of post-MRD+. Results: A total of 335 patients with Ph– high-risk B-ALL were enrolled, including 145 and 190, respectively, in the HID and MSD groups. The 3-year cumulative incidence of post-MRD+ was 27.2% (95% confidence interval [CI]: 20.2%–34.7%) and 42.6% (35.5%–49.6%) in the HID and MSD groups (P = 0.003), respectively. A total of 156 patients received DLI, including 60 (41.4%) and 96 (50.5%), respectively, in the HID and MSD groups ( P = 0.096). The 3-year cumulative incidence of relapse was 18.6% (95% CI: 12.7%–25.4%) and 25.9% (19.9%–32.3%; P = 0.116) in the two groups, respectively. The 3-year overall survival (OS) was 67.4% (95% CI: 59.1%–74.4%) and 61.6% (54.2%–68.1%; P = 0.382), leukemia-free survival (LFS) was 63.4% (95% CI: 55.0%–70.7%) and 58.2% (50.8%–64.9%; P = 0.429), and GVHD-free/relapse-free survival (GRFS) was 51.7% (95% CI: 43.3%–59.5%) and 37.8% (30.9%–44.6%; P = 0.041), respectively, in the HID and MSD groups. Conclusion: HID transplantation has a lower incidence of post-MRD+ than MSD transplantation, suggesting that HID transplantation might have a superior GVL effect than MSD transplantation for Ph– high-risk B-ALL patients. Trial registration: ClinicalTrials.gov: NCT01883180, NCT02673008.